The Effectiveness of the Cooperative Think Pair Share Learning Model in Improving Arabic Writing Skills - Fatimah, Nia Rindah; Murdiono, Murdiono; Thoyyibah, Anisatu (Study Program of Arabic Language Teaching, 2024)
This study aims to determine the effectiveness of the cooperative think pair share learning model to improve writing skills in grades VIII A and VIII B SMP Muhammadiyah 06 Malang. In this study, researchers used a quantitative approach with a quasi-experimental type and a non-equivalent control group design. This study uses the purposive sampling technique. The population is all students at SMP Muhammadiyah 6 Malang, totaling 105 students. The sample consists of 2 classes, namely class VIII A, which is an experimental class that applies the cooperative think pair share learning model. Class VIII B is a control class using lecture methods. The data source is taken from student tests and interview results. Data collection methods use observations, interviews, tests, and documentation. The data analysis techniques used for this study are independent sample t-test and effectiveness test or N-Gain test. The study results obtained a significant difference between the average grades of students before and after the implementation of the think pair share learning model. This can be seen from the average value of the control class of 65.43 while the average value of the experiment class is 76.86 so it can be known that the average value of the experimental class > the control class. The next result uses the N-Gain formula, obtained by 45 with a moderate category. In this case, it can be concluded that the cooperative think pair share learning model is effective in improving writing skills in class VIII A SMP Muhammadiyah 06 Malang.